Stereological and immunogold studies on TIE1 and TIE2 localization in glomeruli indicate angiopoietin signaling in podocytes. (June 2017) - Logothetidou, Anastasia; De Spiegelaere, Ward; Van den Broeck, Wim; Vandecasteele, Tim; Couck, Liesbeth; Simoens, Paul; Cornillie, Pieter
Highlights: Subcellular localization of TIE1 and TIE2 was demonstrated. TIE receptors found in endothelium and podocytes processes were quantified. ANGPT-TIE signaling in podocytes is suggested. Abstract: Angiopoietins and their TIE receptors are important regulators of vascular stability and remodeling. These molecules are involved not only in the normal development of kidney glomeruli, but also in disease, thus making them promising targets for therapies. Although TIE receptors are mainly found in endothelial cells, some reports observed TIE2 expression in glomerular podocytes as well. This suggests a role of angiopoietins in the regulation of podocytes. In the present study, we aimed to map the subcellular localization of TIE receptors in metanephric glomeruli of fetal pigs using high-resolution immunogold electron microscopy and the relative labeling index stereological approach. TIE1 and TIE2 antibody labeling was detected on the abluminal side of endothelial cell membranes. In endothelial cells, 4.5% of TIE2 was observed close to cell–cell contacts and 11.9% of TIE2 was found in closely associated pairs, which suggests the presence of homodimers. Interestingly, both receptors were also expressed in podocyte foot processes indicating that TIE1 and TIE2 may play a similar role in podocytes as in endothelial cells.